Asymmetric Price Transmission in Supply Function Equilibrium, Carbon Prices and the German Electricity Spot Market - Nikolas Wölfing (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
In January 2007, first evidence of an asymmetric pass-through of CO2 emission allowance prices was reported for the German electricity spot market. This paper explores the theoretical basis for such an asymmetry in the context of a supply function bidding duopoly. It interprets fluctuating carbon prices as a coordination mechanism for tacitly colluding firms and studies incentive compatibility in the repeated game. It is new in its attempt to model asymmetric behaviour in a spot market without relevant frictions, and gives a reasoning why the asymmetry shows up for emission allowances only. The paper concludes with a theorem: that asymmetric price transmission is sustained up to a certain maximum level which might include the monopoly solution and that this mechanism is always preferred to non-cooperation.
Keywords: D82; C73; Q41; L13; 330; Asymmetric price transmission; Electricity spot markets; Emission allowances; Emissionsrechte; Preis; Stromtarif; Warenbörse; Wertpapierhandel; Ökonomischer Anreiz; Auktionstheorie; Theorie; Deutschland